(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the experience of sustainable investment development in East and Southeast Asian countries, focusing on institutional mechanisms and the integration of Environmental, Social, and Governance (ESG) principles into investment processes. Using the cases of China, Japan, South Korea, Singapore, Indonesia, Malaysia, and Vietnam, the study analyzes the practical implementation of green finance instruments, green bonds, green sukuk, renewable energy projects, and decarbonization strategies. The paper also identifies the key drivers, challenges, and future prospects of sustainable investment development in the region.